P233 Death and the Respiratory Physician: Challenges to Providing Optimal End-Of-Life Care by Generalists. (19th November 2012) - Smith, LJ; Vergnaud, S; Wright, H; Bates, C
Abstract : Background: Surveys show most patients want to die at home. However 53% of all UK deaths occur in hospital. Patients with chronic respiratory disease are more likely to die in hospital (66% of COPD deaths) yet hospital end of life care is often poor. Clinicians are advised to use the 'surprise question' to identify patients that need advance care planning (ACP). Do not attempt resuscitation (DNAR) orders (evidence of ACP) are often not completed. Barriers previously identified include: lack of training, time, appropriate opportunity and experience; personal discomfort; and perceived lack of patients'/carers' understanding. Objective: We investigated experiences, beliefs and attitudes of doctors in a district general hospital towards end of life care, focusing on issues relevant to Respiratory patients. Methods: Clinicians of varying grades were invited to complete a multiple-choice questionnaire during 'Dying Matters Awareness Week 2012'. Results: Amongst the 73 doctors (49% male) there was a high degree of confidence (eg 76% agreed or strongly agreed that they were comfortable talking to patients/relatives about death and dying).However this did not correlate with familiarity with the 'surprise question' (23% said they were familiar but only 3% gave a correct response), or knowledge of the most distressing end of life symptom (only 18% identified shortness of breath correctly), or knowledge of the patient group with the highest unmet palliative care needs (only 23% identified patients with Respiratory diseases). 40% believed "palliative care is a specialist skill that should be delivered by specialists". Discussion: There is a pressing need for greater expertise in general palliative care amongst hospital doctors. Patients with COPD and other progressive respiratory conditions have extensive palliative care needs. Accurate prognostication is challenging; the surprise question is useful in prompting ACP. DNAR decisions and ACP should not be left to the last days of life. We identified a mismatch between knowledge and confidence levels in our sample. Lack of awareness of their need for education may represent a barrier to doctors accessing training. Respiratory physicians are well placed to lead improvements in ACP and general palliative care in hospital.